The Role of Environmental Auditing in Evaluating Environmental Performance in Industrial Companies: An Exploratory Study of The Opinions of a Sample of Auditors and Academics in The City of Erbil - Arshad Sedeeq Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The research aims to determine the role of environmental auditing in achieving the evaluation of the environmental performance of industrial companies, by the survey the opinions of a sample of auditors and academics in the city of Erbil. The research problem revolves around the rapid changes and developments in the environment of industrial companies, which forced the managements of industrial companies to keep pace with these developments and changes in the business environment and adapt with them to achieve their goals. In order to test the research hypotheses, the questionnaire was designed and distributed to a sample of auditors and academics in the city of Erbil, and then analyzed the data obtained through the use of the (SPSS V.26) program. Accordingly, a number of conclusions were reached, the most important of which is that there is a statistically significant relationship between the environmental audit variable and the environmental performance variable from the point of view of auditors and academics in the city of Erbil, as the value of the correlation coefficient between the two variables reached (0.764) and at a significant level (0.05). This is because the higher the levels of environmental auditing, the higher the levels of environmental performance, by (76.4%), and vice versa. The results of the research showed that there is a significant effect of the variable (environmental auditing) on the variable (environmental performance), depending on the value of the level of significance for the test (F) of (0.000), which was less than the level of significance assumed in the study concerned (0.05), as well as through the value calculated for the test (F), amounting to (93.653), which was greater than its tabular value (3.99). The research recommended the need to compel audit offices in the Kurdistan Region to contribute to activating the role of auditors when auditing and evaluating environmental performance in companies and working to make environmental auditing a mandatory audit and finding the necessary standards that help auditors to audit and evaluate environmental performance